Synthesis of polyfunctionalized benzo[d]thiazoles as novel anthranilic acid derivatives. Issue 27 (1st July 2015) - Hédou, Damien; Harari, Marine; Godeau, Julien; Dubouilh-Benard, Carole; Fruit, Corinne; Besson, Thierry
Graphical abstract Synthesis of versatile polyfunctionalized benzothiazoles as relevant molecular platforms for the synthesis of innovative heterocyclic systems.